Review : Metode Peningkatan Kelarutan Dengan Dispersi Padat - Elpa Giovana Zola; Salman Umar; Erizal Zaini (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
One or more active chemicals are dispersed in a matrix or carrier in an inert state using a solid dispersion technique. The term